ANALISIS PERILAKU ORGANISASI UNTUK MENCAPAI EFEKTIVITAS ORGANISASI PADA ORMAWA FAKULTAS EKONOMI (UNG) - Ikal Taha; Valentina Monoarfa; Muhamad Taufik Kadir; Nur Syafira Aulia Fatihah (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2022)
This study aims to determine the behavior in the organization to achieve organizational effectiveness through (individual behavior, group behavior, and organizational systems). and also an analysis of the factors that affect organizational effectiveness that are considered relevant, including human resources owned by student organizations and leadership. Every organization has organizational goals, organizational goals are to achieve or realize desires, every student who joins the organization is expected to be able to work together in achieving organizational goals. The general purpose of student organizations is as a means of self-development of students towards broadening their horizons in increasing intellectuality and personality integrity. The results of the research and analysis found that the effectiveness of a student organization is seen from the ability of students in terms of the members of the organization being able to adapt to their organizational activities, both academic and non-academic activities, while the influencing factors indicate that the human resources of the organization within the faculty of economics are adequate in utilization and placement is optimal, this can be seen from the interpersonal role, informational role and the influence of the organizational culture.